Incidence and management of chemotherapy-induced nausea and vomiting in women with breast cancer - Thais de Oliveira Gozzo; Sarah Gomes de Souza; Aline Maria Bonini Moysés; Marislei Sanches Panobianco; Ana Maria de Almeida
The objective of this study was to analyze the incidence of chemotherapy-induced nausea and vomiting in women with breast cancer and identify strategies used by them to control these signs and symptoms. Data for this cross-sectional study were collected through interviews during the last cycle of chemotherapy, between August 2011 and March 2012, in a university hospital in the State of São Paulo. The sample consisted of 22 women between the ages of 31 and 70, of whom 77.3% reported nausea and 50% vomiting during treatment. Regarding symptom management, 82% of the women reported having received some information centered on the use of prescribed medication. However, 27.3% did not know what medication they had taken. We concluded that there is a lack of systematic care and institutional protocol to guide professionals in providing standardized information to women so they can better control nausea and vomiting.